A comparison of different indicators of chaos based on the deviation vectors: application to symplectic mappings - Maffione, Nicolás Pablo (2011)
Fil: Maffione, Nicolás P. Universidad Nacional de La Plata. Facultad de Ciencias Astronómicas y Geofísicas. IALP-UNLP-CONICET; Argentina.